Bayam Crispy: Produk Inovasi Daun Bayam Sebagai Upaya Pemberdayaan Masyarakat di Kelurahan Plosokerep, Kecamatan Sananwetan, Kota Blitar - Alweni Alweni; Ayundha Evanthy (Jurnal Pelayanan Hubungan Masyarakat, 2023)
This journal discusses assistance to members of KWT Aren Asri and explains the utilization of spinach leaves which can be said to be quite abundant in the Plosokerep Village, Sananwetan District. The reason for choosing KWT Aren Asri is because the KWT has a great opportunity to be developed. Seeing the potential that exists, it was decided to innovate by managing spinach leaves to become crispy spinach. Spinach leaf plants can be used as products that are processed in an innovative way, but the processed plant products are still not varied. The purpose of this community service activity is to increase the knowledge of Group 34 members to manage spinach plants to become Crispy Spinach. Partners in this community service activity are members of KWT Aren Asri RT 02 RW 06 Plosokerep Village, Sananwetan District, Blitar City. In this community service the method used is by conducting surveys, product manufacturing practices, and explaining material regarding packaging and products through counseling. Members of KWT Aren Asri RT 02 RW 06 Plosokerep Village, Sananwetan District, Blitar City seemed very enthusiastic about the material on how to manage spinach plants into Crispy Spinach products. In addition, KWT Aren Asri members are also very interested in practicing their own ways of making processed innovations from spinach. This community service activity produces Crispy Spinach processed products from spinach plants.